Encyclopaedia Britannica 2005 deluxe CD - Encyclopaedia Britannica, Inc. (Australia : Encyclopaedia Britannica, 2005)
Contains 83,000 articles, World atlas with over 1638 maps, Meriam-Webter's Collegiate dictionary and thesaurus magazine and Web site links, and the Britannica BrainStomer
System requirements for Windows:Microsoft windows 98 SE, 2000,Me,XP., Pentium 350 MHz, or faster processor, 256 MB RAM, 550 MB free hard-disk space, CD-ROm drive, 500x600 resolution, 16-bit colour, mouse,sound card and speaker
System requirements for Macintosh : Mac OS 10.3, iMac or G3 350 MHz or faster processor, 256 MB RAM, 550 MB free hard-disk space, CD-ROm drive, 800 x 600 resolution, mouse, sound card and speakers
Keywords: Electronic encyclopedias; Encyclopedias and dictionaries